An updated synthesis of [11C]carfentanil for positron emission tomography (PET) imaging of the μ‐opioid receptor. (12th May 2017) - Blecha, Joseph E.; Henderson, Bradford D.; Hockley, Brian G.; VanBrocklin, Henry F.; Zubieta, Jon‐Kar; DaSilva, Alexandre F.; Kilbourn, Michael R.; Koeppe, Robert A.; Scott, Peter J.H.; Shao, Xia
Abstract : [ 11 C]Carfentanil ([ 11 C]CFN) is a selective radiotracer for in vivo positron emission tomography imaging studies of the μ‐opioid system that, in our laboratories, is synthesized by methylation of the corresponding carboxylate precursor with [ 11 C]MeOTf, and purified using a C2 solid‐phase extraction cartridge. Changes in the commercial availability of common C2 cartridges have necessitated future proofing the synthesis of [ 11 C]CFN to maintain reliable delivery of the radiotracer for clinical imaging studies. An updated synthesis of [ 11 C]CFN is reported that replaces a now obsolete purification cartridge with a new commercially available version and also substitutes the organic solvents used in traditional production methods with ethanol. Abstract : [ 11 C]Carfentanil ([ 11 C]CFN), a radiotracer for in vivo PET imaging of the μ‐opioid system, is synthesized by methylation of the carboxylate precursor with [11C]MeOTf and purified using a C2 solid‐phase extraction cartridge. Changes in the commercial availability of common C2 cartridges have necessitated future proofing the synthesis of [11C]CFN. An updated synthesis of [11C]CFN is reported, which replaces a now obsolete purification cartridge with a new commercially available version and also substitutes the organic solvents used in traditional production methods with ethanol.